PENGEMBANGAN MATERI PENYESUAIAN DIRI SISWA - Sukarti '; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: One of attempts to be carried out in order to build good, health and dynamicrelationship is the how someone can adjust himself to his surrounding. Adjusting oneselfinfluences students much in classroom not only for self-acceptance in classroom environmentbut also in learning process. Hence, the material services needs to be develop to be a materialregarding students’ self –adjustment that is expected to applied by guidance and counselingteachers to be taught to their students. The objectives of this research are This study aims at (1)to arrange the material for students’ character building based on the clarity, the systematic, thesupporting pictures, the instruments, the novelty of material, and the supporting of game andvideo, (2) to know the result of the students’ character building quality. The material isarranged by using research and development method, then it is experimented to the studentswith the time allocated is 4 lesson hours (4 x 45’). This material is validated by first and secondguidance lectures, guidance and counseling teacher,and the students of SMA 14 Pekanbaru.The materials consist of the definition of self-adjustment, the factors of self adjustment, thekinds of self adjustment and the tips to have good self-adjustment. The result of the materialdevelopment is the arrangement a self-adjustment module with the material quality is in “VeryGood” category with the score obtained 4,22 for the whole aspects of assessment.Keywords : Guidance And Counseling, Self-Adjustment,Senior High School